Solid lipid nanoparticle formulation and antihyperglycemic activity test of sea cucumber (Stichopus hermanii) - Rahmadani, Rahmadani (Indonesian Journal of Multidisciplinary Science, 2023)
This study aims to develop a formulation with the active ingredient Stichopus hermanii for antidiabetic treatment or function to lower blood glucose levels. The formulation approach taken is to design a formula in the form of solid lipid nanoparticles (SLN), where this system is expected to optimize absorption and improve the performance of the active substance. The SLN characterization includes particle size measurement, zeta potential, polydispersity index analysis, and morphology analysis using TEM. The antihyperglycemic activity test will be tested in vivo using male white rats using the glucose tolerance test method and induced by streptozotocin. The results of the TEM analysis showed that the sea cucumber spherical in shape. The particle size of the formula was found to be 0.25 nm. The polydispersion index (PDI) of the formulation was 67.5%, 2%, and 0.5%, respectively. In the same test, male rats were given treatment according to the group division, namely 50% glucose at a dose of 3 g/kg bw 30 minutes later and the blood sugar levels were measured at 30, 60, 90, and 120 minutes using a glucometer. In a follow-up test, the administration of test samples (days -3, 6, 9, 12, and 15) of CMC Na, metformin, and 25 mg/kg body weight of the test group showed that blood sugar level decreased with the highest decrease in positive control group. In conclusion, the results showed that sea cucumbers could be developed as a functional food product to help battle the onset of diabetes and diabetic complications.